Physiological characterization and regulation of the contractile properties of the mosquito ventral diverticulum (crop). (November 2017) - Calkins, Travis L.; DeLaat, Andrew; Piermarini, Peter M.
Graphical abstract: Highlights: Spontaneous contractions of the mosquito crop in vitro are calcium dependent. The contractions are enhanced by serotonin and cAMP, and inhibited by benzethonium chloride. Inhibitors of protein kinase A and gap junctions reduce crop contractions. Innexin mRNAs and proteins are expressed in the crop. Abstract: In adult dipteran insects (flies), the crop is a diverticulum of the esophagus that serves as a food storage organ. The crop pumps stored contents into the alimentary canal for digestion and absorption. The pumping is mediated by peristaltic contractions of the crop musculature. In adult female mosquitoes, the crop (ventral diverticulum) selectively stores sugar solutions (e.g., nectar); proteinaceous blood meals by-pass the crop and are transferred directly to the midgut for digestion. The mechanisms that regulate crop contractions have never been investigated in mosquitoes. Here we provide the first physiological characterization of the contractile properties of the mosquito crop and explore the mechanisms that regulate crop contractions. Using an in vitro bioassay we found that the isolated crop spontaneously contracts in Ringer solution for at least 1 h and its contractions are dependent on extracellular Ca 2+ . Adding serotonin (5-hydroxytryptamine, 5-HT) or a membrane-permeable analog of cyclic adenosine monophosphate (cAMP) to the extracellular bath increased the frequency of crop contractions. On the other hand, adding benzethonium chloride (BzCl; a chemical that mimics the effects of myosuppressins), H-89 or Rp-cAMPS (inhibitors of protein kinase A, PKA), or carbenoxolone (an inhibitor of gap junctions) reduced the frequency of the unstimulated, spontaneous and/or 5-HT-stimulated crop contractions. Adding aedeskinin III did not detectably alter crop contraction rates. In addition to pharmacological evidence of gap junctions, we demonstrated that the crop expressed several mRNAs encoding gap junctional proteins (i.e. innexins). Furthermore, we localized immunoreactivity for innexin 2 and innexin 3 to muscle and epithelial cells of the crop, respectively. Our results 1) suggest that 5-HT and myosupressins oppositely regulate contractile activity of the mosquito crop, and 2) provide the first evidence for putative roles of cAMP, PKA, and gap junctions in modulating contractile activity of the dipteran crop.